X‐linked retinoschisis: an update - Sikkink, Stephen K (BMJ Group, 2007)
X‐linked retinoschisis is the leading cause of macular degeneration in males and leads to splitting within the inner retinal layers leading to visual deterioration. Many missense and protein truncating mutations have now been identified in the causative retinoschisis gene (RS1) which encodes a 224 amino acid secreting retinal protein, retinoschisin. Retinoschisin octamerises is implicated in cell–cell interactions and cell adhesion perhaps by interacting with β2 laminin. Mutations cause loss of retinoschisin function by one of the three mechanisms: by interfering with protein secretion, by preventing its octamerisation or by reducing function in the secreted octamerised protein. The development of retinoschisis mouse models have provided a model system that closely resembles the human disease. Recent reports of RS1 gene transfer to these models and the sustained restoration of some retinal function and morphology suggest gene replacement may be a possible future therapy for patients.